Analysis of the state of vegetation cover using remote sensing data - Shamsiev Z. Z.; Sulyukova L. F.; Shamsiev R. Z. (E3S Web of Conferences)
The article discusses the processing of satellite images using various methods for monitoring the state of vegetation. The complex application of vegetation property identification indices made it possible to assess the level of influence of various environmental factors showing the deterioration of vegetation cover in foothill areas. As a result, obtained, the uneven distribution of vegetation cover was determined using vegetation, soil, and water indices. Large and small areas of plant, aquatic, and soil objects have been identified that are interconnected according to various criteria, such as salinity, humidity, and high thermal brightness characteristics of the Earth's surface. A comparative assessment of the results obtained with official data from meteorological services is given.